O uso do sistema construtivo Insulated Concrete Forms (ICFs) na construção civil brasileira - Chagas, Matheus Vilar (Brasil, 2024)
The project in question focuses on analyzing and comparing the costs of the Insulated Concrete Forms (ICF) construction method with the traditional construction method, particularly considering the criteria established by the performance standard NBR 15575 applied to an individual house. The main objective is to demonstrate the economic and technical feasibility of ICF in the Brazilian construction industry. To achieve this goal, the study describes the stages of the construction process with ICF, from the beginning of the project to the completion of the work, emphasizing technical aspects and potential benefits compared to the conventional method. The methodology used included collecting data on the cost-benefit ratio of both ICF and the conventional method, using specific metrics from the Brazilian market. The comparative analysis was based on the requirements of the NBR 15575 standard, which evaluates the performance of residences, with the aim of identifying significant differences in terms of energy efficiency, thermal comfort, acoustic comfort, and durability. The results obtained highlight the superiority of the ICF system in several analyzed aspects, demonstrating its greater economic attractiveness due to a 10.11% reduction compared to the ceramic block masonry method, as well as providing a more comfortable and sustainable indoor environment. In conclusion, the use of the ICF system emerges as a viable and effective alternative for the construction sector, offering not only economic benefits but also positively contributing to environmental issues and structural performance in accordance with current regulatory requirements.